2022
DOI: 10.1186/s12876-022-02174-4
|View full text |Cite
|
Sign up to set email alerts
|

Fecal indicator bacteria along multiple environmental exposure pathways (water, food, and soil) and intestinal parasites among children in the rural northwest Ethiopia

Abstract: Background Children in low-resource settings are exposed to multiple risk factors for enteropathogens. However, the probability of exposures may be different across exposure pathways. Accordingly, this study was conducted to assess environmental exposures of children to intestinal parasites in the east Dembiya district of Ethiopia. Methods A cross-sectional study was conducted for 372 households with children aged 24–59 months. The potential for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…This community-based cross-sectional study is part of a large-scale study conducted in rural northwest Ethiopia during May–June 2021 to assess environmental exposures of children to enteric infections and fecal biomarkers of EED in children aged 24–59 months. The method has been described in more detail elsewhere 38 , 39 . The sample size was determined using double proportion population formula with the following assumptions: proportion of stunting with enteric infection (p 1 ) = 38.5%, proportion of stunting with no enteric infection (p 2 ) = 61.5% 40 , Z α/2 at type I error of 5% = 1.96, Z β at 80% power = 0.842, and an allocation ratio of 1:1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This community-based cross-sectional study is part of a large-scale study conducted in rural northwest Ethiopia during May–June 2021 to assess environmental exposures of children to enteric infections and fecal biomarkers of EED in children aged 24–59 months. The method has been described in more detail elsewhere 38 , 39 . The sample size was determined using double proportion population formula with the following assumptions: proportion of stunting with enteric infection (p 1 ) = 38.5%, proportion of stunting with no enteric infection (p 2 ) = 61.5% 40 , Z α/2 at type I error of 5% = 1.96, Z β at 80% power = 0.842, and an allocation ratio of 1:1.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal contamination of the living environment (drinking water, ready-to-eat foods, and courtyard soil) was measured by detection of fecal indicator bacteria, i.e., Escherichia coli ( E. coli ) using membrane filter technique 46 . Sampling procedures of environmental samples and E. coli detection procedures are described elsewhere in more detail 38 . Intestinal parasites in children were measured by detecting ova of one or more intestinal parasites in stool samples of children using wet mount and Kato-Katz techniques 47 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several water-borne diseases due to contaminated groundwater are constantly being reported across the globe irrespective of the economic status of the region (Zhang et al 2014;Andrade et al 2018). E. coli is regularly used as an indicator organism to check faecal discharges and ensure biological safety of water sources (Navab-Daneshmand et al 2018;Gizaw et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A study done to measure child exposure to enteric infection in the rural northwest Ethiopia showed that contamination of water, food, and soil with fecal matter due to open defecation practice and poor animal keeping practice was common. Moreover, mouthing of soil or soil contaminated materials is commonly practiced among children in the rural Ethiopia 3 .…”
Section: Introductionmentioning
confidence: 99%